Developing a prototype for short-term psychodynamic (supportive-expressive) therapy: An empirical study with the psychotherapy process Q-set. (3rd July 2016) - Leichsenring, Falk; Ablon, Stuart; Barber, Jacques P.; Beutel, Manfred; Gibbons, Mary Beth Connolly; Crits-Christoph, Paul; Klein, Susanne; Leweke, Frank; Steinert, Christiane; Wiltink, Jörg; Salzer, Simone
Abstract: Objective : A Psychotherapy Process Q-set (PQS) prototype characteristic of short-term psychodynamic therapy (STPP) does not yet exist.Method : Experts in supportive-expressive (SE) therapy used the 100-Item PQS questionnaire to rate an ideal short-term SE therapy.Results : Agreement between raters was high (Cronbach's alpha = 0.94). The prototype for SE therapy showed a significant correlation with the psychoanalytic prototype, but with 28% of variance explained, the majority of variance of the former was not explained by the latter or vice versa. Furthermore, the SE prototype showed significant correlations with the cognitive-behavioral prototype and the prototype of interpersonal therapy by Ablon and Jones ( r = 0.69, 0.43).Conclusions : We recommend using the PQS prototype presented here for future process research on STPP.